Penurunan Kadar COD Pada Limbah Cair Laboratorium Menggunakan Sorben Hydrilla Verticillata - Agipa, Ade Irmadiki; Ruspita, Roza; Muarif, Muhamad Fajar; Jannah, Al Baasiqot Shoffia Nur (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
Hydrilla Verticillata adsorbents, HCl-activated Hydrilla Verticillata, and NaOH-activated Hydrilla Verticillata reduce COD levels in laboratory waste. The sorbents were characterized using FTIR and SEM-EDX. FTIR analysis shows a specific absorption at the wave number 1637 cm-1, which indicates the absorption of the carbonyl group in the ester and 1536, 1416, and 1324 cm-1, identical to the absorption of the carboxyl group. SEM results show a hollow and irregular shape in the sorbent. EDX analysis showed that Hydrilla Verticillata, which was activated using HCl and NaOH, experienced a decrease in the percentage of metals. Testing for COD levels in laboratory waste before treatment was 29,492 ppm. Adsorption with various types of sorbents caused a decrease in COD levels to 25,430, 25,424, and 26,441 ppm for the Hydrilla Verticillata, HCl-activated Hydrilla Verticillata and NaOH-activated Hydrilla Verticillata sorbents. Varying concentrations of 0.03, 0.04, 0.05, 0.06, and 0.07 M on HCl-activated Hydrilla Verticillata Sorben showed a reduction in COD levels of 17.24%, 12.07%, 6.90%, 13.79%, and 20.69%.